Cryptocurrency based on Blockchain Technology (Global Journal of Computer Science and Technology, 2023)
The state of Palestine does not own national currency so Palestine loses a lot of money yearly due to the use of foreign currencies and the Paris Protocol agreement prevents Palestinian own currency For that the crypto-currencies based on block-chain instead of physical currency will help the state of Palestine to avoid the obstacles that prevent to own currency In this paper we will study the cryptocurrency based on Blockchain technology that uses peer-to-peer P2P and timestamp server In additional exploring the main components of bitcoin currency as an example
Keywords: blockchain; P2P; timestamp; digital currency; cryptocurrency; bitcoin